The Bataan Nuclear Power Plant three episodes of decision making - Cardenas, Benito C. (1987)
The controversial construction of the first Philippine Nuclear Power Plant (PNPP-1) in Bataan is subjected to a dose examination in the area of decision making. The entire decision-making process is analyzed in three parts or episodes. The first begins with the blueprint stage of the PNPP-1 where the rational model of Etzioni is applied. The temporary suspension of the PNPP-1 construction constitutes the second episode. This is an attempt to apply Lindblom 's incrementalist model with the subsequent decision by President Marcos to resume the construction of PNPP-1 as a reversion to the application of the rational model. Under President Aquino's administration, the third episode junking the PNPP-1 makes use of a combination of the two models-incrementalism and mixed scanning with Simon's satisficing model-which proves to be more effective in making policy decisions.
Keywords: Nuclear power plants; Nuclear power plants -- Risk assessment; Bataan Nuclear Power Plant